Talent Management Strategies for Navigating Organizational Digital Transformation - Agustin; Firdaus; Nurcahyati (Economy, Business, Finance, Accounting & Management Journal, 2025)
Digital transformation has become a strategic necessity for organizations as they navigate technological advancements, shifting business models, and intensifying global competition. In this context, talent management plays a critical role in ensuring the availability of human resources with digital competencies, adaptability, and the readiness to navigate organizational change. This study aims to analyze effective talent management strategies that support the success of an organization’s digital transformation. The research method employed is a quantitative approach using a survey technique targeting employees and managers across various organizations currently implementing digital transformation. Data was collected via questionnaires and analyzed using descriptive statistics and linear regression. The results indicate that talent management strategies encompassing talent identification, digital competency development, succession planning, and employee retention have a positive and significant impact on the success of an organization’s digital transformation. Additionally, technology-based training programs and a culture of continuous learning have been shown to enhance employees’ readiness to adopt digital changes. In conclusion, the implementation of integrated talent management strategies focused on developing digital competencies is a key factor in enhancing competitiveness and supporting the sustainable success of an organization’s digital transformation.